Plugging efficiency of flaky and fibrous lost circulation materials in different carrier fluid systems - Alhaidari, Saleh A.; Alarifi, Sulaiman A.; Bahamdan, Abdulaziz (Frontiers in Physics, 2022)
Lost circulation is one of the most significant contributors to wellbore instability and causes an increase in drilling operation costs. It is also a major contributor to the nonproductive time and must be minimized for improved economic and operational performance. The objective of this research is to provide tools and information about specific loss circulation management techniques that drillers can use to minimize lost circulation. This study involves comprehensive approaches to test the plugging efficiency of three different lost circulation materials (LCMs) from two groups of materials (Flaky and Fibrous). It also highlights the carrier fluids (drilling fluids) and the determination of the optimum drilling fluids properties. Different fracture sizes and the effect of the various LCM are analyzed. The impact of LCM’s shape, size and physical and chemical properties along with the fracture sizes are discussed. Examining the particle size distribution before and after mixing with the fluids shows the capability of the materials in plugging the fracture while maintaining the minimum porosity and permeability of the plug. It also helps to strengthen the fracture gradient of the formation by knowing the actual particles sizes. The primary objective of this work is to precisely study and analyze these factors on the three LCMs along with different carrier fluids to investigate their plugging efficiency and potentially resolve the or minimize the severity of the lost circulation problem.